Assessing awareness, knowledge, and perceptions of hubbly bubbly smoking health risks among South African university students. - Motloutsi, Aniekie; Lubinga, Elizabeth (Communicare, 2023)
Globally, the smoking of hubbly bubbly tobacco pipes is a growing trend among young people. However, the promotion of health awareness about hubbly bubbly (HB) smoking risks does not appear to be common, especially in South Africa. This study intended to assess awareness of the HB smoking health risks among students; to determine the students' knowledge levels about its risks; to examine the students' perceptions of HB smoking and to determine whether their knowledge and perceptions on smoking health risks would influence their HB smoking behaviour intentions. The Extended Parallel Process Model was applied. A quantitative approach was applied with a sample of 350 students participating in the study: n = 175 HB users and n = 175 non-users. A 2×2 experimental design between and within participants was followed. Results indicate that most participants (75%) had not heard or seen any health communication awareness campaigns about HB risks and that knowledge about HB smoking health risks was inadequate. Most participants in the study, including both HB users 74% (129) and non-users 80% (140), were able to identify lung cancer as one of the health risks of HB smoking. This study is important to health promotion organisations including government departments to enable them to construct effective health communication messages.